Rejection of Impassable Substrates by Yersinia Type III Secretion Machines - Sorg, Joseph A. (American Society for Microbiology, 2005)
Type III machines of pathogenic Yersinia spp. transport Yop proteins across the bacterial envelope into host cells. Translational fusions of yopE to the dihydrofolate reductase gene (dhfr) or the β-galactosidase gene (lacZ) generate hybrid proteins that block type III injection of Yop proteins into host cells, consistent with the canonical view that impassable DHFR and LacZ hybrids jam secretion machines. Mutations in repressors of posttranscriptional gene regulation, Yersinia enterocolitica yscM1 and yscM2 as well as Yersinia pestis lcrQ, relieve the YopE-DHFR-imposed blockade and restore type III injection into host cells. Genetic suppression of the type III blockade does not, however, promote YopE-DHFR secretion. A model is proposed whereby rejection of YopE-DHFR from the secretion pathway inhibits type III gene expression.